A reversible connection for robotic assembly of timber structures. (15th October 2021) - Hansen, Søren Gustenhoff; Kunic, Anja; Naboni, Roberto
Highlights: New timber connection for automated robotic assembly. Robotic CNC-fabrication. Experimental programme. Mechanical shear model. Abstract: The advent of Robotic Timber Assembly is offering exciting possibilities and challenges for structural developments. This research proposes a new concept of timber connections used in automated robotic assembly and disassembly. The connection presents some interesting features: it facilitates self-alignment during the construction process, it provides enhanced shear capacity compared to conventional connections, and it has ductile behaviour. The paper presents an experimental programme to investigate the shear capacity and the influence of essential design parameters. Detailed displacement measurement through Digital Image Correlation allows the deduction of the connection's exact load response. An analytical model is derived based on the observed failure mechanisms and compared with experimental results for validation. The results show the good accuracy of the developed calculation models.